Air pollution and mortality in Valencia, Spain: a study using the APHEA methodology. Issue 5 (October 1996) - Ballester, F; Corella, D; Pérez-Hoyos, S; Hervás, A
Abstract : STUDY OBJECTIVE: To assess the short term relationship between daily air pollution indicators (black smoke and sulphur dioxide (SO2)) and mortality in Valencia. DESIGN: This was an ecological study using time series data with application of Poisson regression. Daily variations in four selected outcome variables (total mortality, mortality in those over 70 years of age, and cardiovascular and respiratory mortality) were considered in relation to daily variations in air pollution levels for the period 1991-93. SETTING: The city of Valencia, Spain. MAIN RESULTS: The mean daily mortality was 17.5, and the average daily levels of air pollutants from the three monitoring stations included in the study were, 67.7 micrograms/m3 for black smoke, and 39.9 micrograms/ m3 for SO2. A significant positive association between black smoke and three of the four outcomes in the study was found. The estimated relative risk (RR) of dying corresponding to a 10 micrograms/m3 increase in mean daily black smoke over the whole period was 1.009 (95% confidence interval (95% CI): 1.003, 1.015). For mortality in the group aged more than 70 years and for cardiovascular mortality, the RRs were 1.008 (95% CI: 1.001, 1.016) and 1.012 (95% CI: 1.003, 1.022) respectively. The association with SO2 was less clear: it was only evident during the warm season. The estimated RRs in this case were 1.007 (95% CI: 0.999, 1.015) for total mortality, 1.009 (95% CI: 1.00, 1.21) for total mortality in those older than 70, and 1.012 (95% CI: 0.995, 1.026) for cardiovascular deaths. No significant association was found between mortality from respiratory diseases and either of the two pollutants. CONCLUSIONS: A positive relationship between air pollution and mortality was found in the short term, as has been shown in an important number of studies carried out elsewhere. Although the current levels of particulate air pollution in Valencia are not very high, they could have an effect on the number of premature deaths. Despite the fact that the association is weak, it is important at the public health level both because of the numbers of population exposed and the possibility of establishing control measures.